Functionalization of α-In2Se3 Monolayer via Adsorption of Small Molecule for Gas Sensing - Xie, Zhi; Yang, Fugui; Xu, Xuee; Lin, Rui; Chen, Limin (Frontiers in Chemistry, 2018)
Based on first-principles calculations, the adsorption of NO and NO2 gas molecules on the α-In2Se3 monolayer have been studied. The adsorption configuration, adsorption energy, electronic structure and charge transfer properties are investigated. It is found that the charge transfer processes of NO and NO2 adsorbed on the surface of α-In2Se3 monolayer exhibit electron donor and acceptor characteristics, respectively. After the adsorption of the molecules, the α-In2Se3 monolayers have new states near the Fermi level induced by NO and NO2, which can trigger some new effects on the conducting and optical properties of the materials, with potential benefits to gas selectivity. The present work provides new valuable results and theoretical foundation for potential applications of the In2Se3-based gas sensor.